If a = b^2 / (b – a), then the value of a^3 + b^3 is: (a) 2 (b) 6ab (c) 0 (d) 1
Given the values for \(a\), \(b\), and \(c\) as: - \(a = \sqrt{6} - \sqrt{5}\) - \(b = \sqrt{5} - 2\) - \(c = 2 - \sqrt{3}\) And using the approximate square root values: - \(\sqrt{6} \approx 2.45\) - \(\sqrt{5} \approx 2.24\) - \(\sqrt{3} \approx 1.73\) We can approximate the values of \(a\), \(b\)Read more
Given the values for \(a\), \(b\), and \(c\) as:
– \(a = \sqrt{6} – \sqrt{5}\)
– \(b = \sqrt{5} – 2\)
– \(c = 2 – \sqrt{3}\)
And using the approximate square root values:
– \(\sqrt{6} \approx 2.45\)
– \(\sqrt{5} \approx 2.24\)
– \(\sqrt{3} \approx 1.73\)
We can approximate the values of \(a\), \(b\), and \(c\) as:
– \(a \approx 2.45 – 2.24 = 0.21\)
– \(b \approx 2.24 – 2 = 0.24\)
– \(c \approx 2 – 1.73 = 0.27\)
Thus, we have the order:
\[
a < b < c
\]
Therefore, the correct alternative among the given options is:
(a) \(a < b < c\)
See less
Given the equation \(a = \frac{b^2}{b-a}\), we can rearrange this equation to find a relationship between \(a\) and \(b\). Multiplying both sides by \(b-a\) gives: \[ a(b - a) = b^2 \] Expanding the left side: \[ ab - a^2 = b^2 \] Rearranging terms: \[ ab = a^2 + b^2 \] Now, we are asked to find theRead more
Given the equation \(a = \frac{b^2}{b-a}\), we can rearrange this equation to find a relationship between \(a\) and \(b\). Multiplying both sides by \(b-a\) gives:
\[
a(b – a) = b^2
\]
Expanding the left side:
\[
ab – a^2 = b^2
\]
Rearranging terms:
\[
ab = a^2 + b^2
\]
Now, we are asked to find the value of \(a^3 + b^3\). We know the identity for the sum of cubes is:
\[
a^3 + b^3 = (a + b)(a^2 – ab + b^2)
\]
Substituting \(ab = a^2 + b^2\) into the identity:
\[
a^3 + b^3 = (a + b)(0)
\]
Since anything multiplied by 0 is 0:
\[
a^3 + b^3 = 0
\]
Therefore, the value of \(a^3 + b^3\) is \(0\), and the correct option is:
(c) 0
See less